Ruptured sinus of Valsalva aneurysm from left coronary sinus into right atrium: a rare anomaly with an odd presentation. (25th March 2013) - Vadivelu, Ramalingam; Rohit, Manoj Kumar; Yadav, Mukesh
Abstract : We report a case of a 42-year-old man presenting with shortness of breath and palpitation on exertion, who was evaluated to have left sinus of Valsalva aneurysm rupturing into right atrium. This is a very rare congenital cardiac anomaly with variable clinical presentation ranging from asymptomatic detection on imaging to acute coronary syndrome and sudden cardiac death. Rupture is the most dreaded complication and usually manifests as an acute event. Aneurysmal dilation less commonly affects the left sinus and rupture into the right atrium is still rarer and a chronic insidious presentation as in this case is odd.